Using Contract Law in the Negotiations of Mergers & Acquisitions - Lahdelma, Sampo (My University, 2019)
ABSTRACT Companies use mergers and acquisitions as a strategic tool in order to carry out their economical and organizational goals. Mergers and acquisitions are often extremely long and complex processes that involve negotiations in a number of subjects. Success in the negotiations require a lot of expertise and input. The thesis focuses on the negotiations conducted in mergers and acquisitions and operating in them. The research problem is the following: which aspects of contract law can the negotiating parties use on in order to achieve the best possible outcome. The theoretical frame of reference the thesis focuses on is mergers and acquisitions in general, the legislation concerning them and their negotiations as well as proceeding in them from both the buyer’s and the seller’s point of view. Mergers and acquisitions as terms are multi-dimensional, but in this thesis, they mainly refer to either the transfer of the business or shares. Regarding the legislation affecting mergers and acquisitions the thesis focuses on the norms affecting the negotiation phase and the contracts agreed in it. The negotiations are studied observing the process possibilities of them and by analysing the most important contractual instruments used in the negotiations and the benefits of them. The research material used in the thesis is mainly Finnish legal literature, but literature specific to the field is also studied and utilized. Behind a merger or an acquisition can be a variety of reasons and aspirations that all affect the negotiations that take place in them. Mergers and acquisitions can have different forms as can the negotiations. There is a variety of process possibilities for conducting the negotiations that affect both the phases of the negotiations and the benefits gained in them. Non-disclosure agreements, preliminary contracts, and the due diligence investigations rise above others with their importance within the instruments of contract law. By using these, as well as the other contract tools, and acknowledging the boundaries set by contract legislation, the negotiating parties can reposition themselves in the negotiation proceedings with the goal being the best possible final contract for an individual.
Keywords: Mergers & Acquisitions; Contract law; Negotiations; fi=Talousoikeus|en=Business Law|; fi=Talousoikeuden maisteriohjelma|en=Master's Programme in Business Law|; Kansainvälinen talousoikeus